Uppkomsten av ett professionellt medicinskt fält Läkares, sjuksköterskors och laboratorieassistenters formering - Carlhed Ydhag, Carina (Stockholm Studies in Education, 2020)
"To analyze the emergence of a professional field means to understand the social processes that take place in the formation of professions in society such as. knowledge, power and social order. Why does the medical profession have such a high status? How come some professions have power over others? What does medical science contribute to professional knowledge? These are some of the questions that this book seeks to answer through a professional sociological analysis. The book is about the growth and professionalization of the Swedish medical field from the Middle Ages to the 1990s, with a focus on three of its professions that have been active there, namely doctors, nurses and biomedical analysts (former laboratory assistants). Books about professions often focus on a profession or an important institution, but there is no book that describes the larger social professional medical field over time. By becoming aware of the field-specific change and development processes and their inertia, one understands that change is very slow and that there are many parameters that must work in the same direction for a real change to take place and be noticed. Other important insights are that the professions themselves are not so strong and dynamic, but that they are dependent on opportunities being opened and closed by external forces, in many cases without their intervention. The book sheds light on how to understand the world around you in a new way, with a critical holistic perspective and with terminology that can help to put into words what is experienced."